2016
DOI: 10.1080/2162402x.2016.1184802
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of tumor cell-derived 5′-deoxy-5′-methylthioadenosine on human T cells

Abstract: The immunosuppressive tumor microenvironment represents one of the main obstacles for immunotherapy of cancer. The tumor milieu is among others shaped by tumor metabolites such as 5 0 -deoxy-5 0 -methylthioadenosine (MTA). Increased intratumoral MTA levels result from a lack of the MTAcatabolizing enzyme methylthioadenosine phosphorylase (MTAP) in tumor cells and are found in various tumor entities. Here, we demonstrate that MTA suppresses proliferation, activation, differentiation, and effector function of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 80 publications
5
36
0
Order By: Relevance
“…It has previously been demonstrated that MTA can directly suppress the proliferation and function of T lymphocytes (24,67). Our findings complement these studies by showing that MTA, which accumulates in MTAP-deficient tumor cells, can also influence innate immune cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It has previously been demonstrated that MTA can directly suppress the proliferation and function of T lymphocytes (24,67). Our findings complement these studies by showing that MTA, which accumulates in MTAP-deficient tumor cells, can also influence innate immune cells.…”
Section: Discussionsupporting
confidence: 88%
“…MTA is known to be functionally active within cells as an inhibitor of methyltransferases (22,23). This metabolite has also been shown to suppress cell proliferation via different, cellular context-dependent mechanisms, including targeting the Akt signal pathway and interfering with intracellular protein methylation in T cells (24), or acting through adenosine receptors on the cell surface of melanoma cell lines (25). Studies on mechanism of pathogen-induced host inflammatory responses have linked MTA to downregulation of TNFα production by macrophages through engaging adenosine receptors (26), and have revealed a role of MTA in controlling host inflammation response, such that MTA has been used as an immunosuppressive drug for treating colitis, liver inflammation, brain inflammation and autoimmunity in animal models (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently shown that alterations in the tumor environment result in high tumoral MTA levels that inhibit protein arginine methylation and suppress anti-cancer human T cell responses. Accumulating evidence therefore hints that the T cell effects of global methyltransferase inhibition are due to inhibition of Protein Arginine Methyl Transferases (PRMT) (29, 30). However, conclusive evidence demonstrating that PRMTs are responsible for T cell suppression, as well as a specific role for the main symmetric dimethylation enzyme PRMT5, has been lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Kynurenine, a breakdown product of tryptophan, can modulate both the innate and adaptive immune system and has been implicated in cancer-associated immunosuppression (Platten et al, 2014) and indoleamine-2,3-dioxygenase (IDO) inhibitors that decrease tryptophan metabolism can help break immune tolerance and potentiate chemotherapy (Muller et al, 2005). Increased MTA levels in MTAP-null tumors can also suppress T cell activation (Henrich et al, 2016) and suggests some metabolic interventions might enhance anti-cancer immune responses.…”
Section: Can Cancer Metabolism Be Exploited To Improve Therapy?mentioning
confidence: 99%